Answer:
x= 17 radical 3
y= 34
Step-by-step explanation:
30-60-90 triangle rule
many students are registered in Bob's class?
I need this ASAP
Answer:
65%
Step-by-step explanation:
You start by dividing 641.29 by 986.60 (641.29/986.60). This gets you .65, which as a percentage is 65%
f(x)=x^2+20x+40
f(x)=x²+20x+40
To complete the square, the same value needs to be added to both sides.
f(x)+?=x²+20x+?+40
Now i make the same thing in different forms ok
To complete the square x²+20x+100=(x+10)² add 100 to the expression
f(x)+?=x²+20x+100+40
Is the same ok you can choose which way you can do
x²+20x+?
write the expression as a product with the factor 2 and x
x²+2x×x10+?
x²+2×x×10+?
Since 10 is part of the middle term, add 10² to the expression
x²+2×x×10+10²
Calculate the product
x²+20x+10²
or evaluate the power
x²+20x+100
f(x) +?=x²+20x+100+40
Since 100 was added to the right - hand side, also add 100 to the left hand side
f(x)+100=x²+20x+100+40
Using a²+2ab+b²=(a+b)², factor the expression
f(x)+100=(x+10)²+40
------------------
x²+20x+100
Write the expression as a product with the factors x and 10
x²+2×x×10+100
Write the number in the exponential form with an exponent of 2
x²+2×x×10+10²
Using a²+2ab+b²=(a+b)² factor the expression
(x+10)²
--------
f(x)+100=(x+10)²+40
Move constant to the right-hand side and change its sign
f(x)=(x+10)²+40-100
Calculate the difference
40-100
Keep the sign of the number with the larger absolute value and subtract the smaller absolute value from the larger
-(100-40)
Subtract the numbers
-60
Answer:f(x)=(x+10)²-60
PLEASE MARK ME AS BRAINLIEST
To rewrite the function f(x) = x² + 20x + 40 by completing the square, we find half the coefficient of the x term, square it, subtract the constant term in the original equation from this squared result, then rewrite the function as (x+10)^2 - 60.
When you're asked to rewrite the function by completing the square, there are certain steps to follow. We start with the function f(x) = x² + 20x + 40.
#SPJ2
Answer:
Job A - Job D - Job E - Job B - Job C
Step-by-step explanation:
Job A = 2
Job B = 10
Job C = 15
Job D = 6
Job E = 8
SJN (Shortest Job Next) is also known as Shortest Job First. In Shortest Job Next, the job with the shortest time among the available jobs is executed first then followed by the next job having the shortest time till all the jobs are finally executed.
Since all the five jobs are already in the queue: they will be processed based on the job having the shortest CPU time among the available job.
Job A will be processed first since it has smallest time of 2, followed by Job D with a time of 6, followed by Job E with a time of 8, followed by Job B with a time of 10 and finally Job C which is processed last.